PSYCHOSOCIAL FACTORS RELATED TO POSTPARTUM BLUES IN DAU DISTRICT, MALANG REGENCY - Kurniawati, Elisa Danik; Wittiarika, Ivon Diah; Al Farizi, Sofia; Lestari, Pudji (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
The postpartum period is a vulnerable period for women due to adaptation to their role as new mothers. This phase requires adjustment because failure to adapt will lead to mental health problems, such as postpartum blues. This study analyzes the psychosocial factors of postpartum blues in Dau district. This research is quantitative research with a cross-sectional design. Data analysis used the Chi-square test. Most respondents had an introverted personality type (56.5%), did not experience anxiety or were normal (39.1%), and had moderate social support (47.8%). The results of the Chi-square test on postpartum blues with personality type showed p-value=0.264 (p>0.05), with anxiety during the postpartum period showing p-value =0.016 (p<0.05), with social support showing p- value =0.020 (p<0.05). There is no significant relationship between postpartum blues and personality type. There is a significant relationship between postpartum blues with postpartum anxiety and social support.